2000
DOI: 10.1080/002073900434369
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of how perceptions of mathematics ability can affect elementary statistics performance

Abstract: This study investigates the eå ects of perceived mathematics ability (PMA) on the learning process with special reference to 147 undergraduates following an elementary statistics (ES) course. A model incorporating PMA together with aptitude, eå ort put in, expected grade, motivation to do well and interest in the subject, which are deemed to be either directly or indirectly associated with performance, is developed. PMA itself is not a good predictor of ES performance, rather its eå ect may be channelled throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Despite the frequently heard argument that understanding and applying statistics to empirical data does not require advanced mathematics (e.g., Galagedera, Woodward, and Degamboda 2000;Lalonde and Gardner 1993), mathematical aptitude accounted for 22% of the variance in statistics achievement while the remaining cognitive and affective variables together explained only 14% of the variance in achievement in statistics. Thus mathematical aptitude turned out to be the most important among the variables used in the current study for modeling the structure of achievement in statistics.…”
Section: Summary and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite the frequently heard argument that understanding and applying statistics to empirical data does not require advanced mathematics (e.g., Galagedera, Woodward, and Degamboda 2000;Lalonde and Gardner 1993), mathematical aptitude accounted for 22% of the variance in statistics achievement while the remaining cognitive and affective variables together explained only 14% of the variance in achievement in statistics. Thus mathematical aptitude turned out to be the most important among the variables used in the current study for modeling the structure of achievement in statistics.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…Mathematical ability and background are frequently discussed in relation to achievement in statistics. Although it is often argued that understanding and applying statistics in empirical research does not require advanced mathematics, a significant and positive relationship between mathematical ability and performance has been consistently reported in the literature (Galagedera 1998;Galagedera, Woodward, and Degamboda 2000;Lalonde and Gardner 1993;Nasser 1998Nasser , 1999Wooten 1998). For example, Galagedera (1998) found that first-year business mathematics and statistics students who were successful in mathematics at the university entry-level examination were more likely to do better in elementary statistics than poor performers at matriculation level.…”
Section: Mathematical Aptitudementioning
confidence: 99%
“…There appears to be a belief that good mathematical skills are essential for learning statistics. However, Galagedera et al [69] found that perceived mathematical abilities have little effect on students' performance in elementary statistics. Much of the literature seems to favor practical approaches over theoretical approaches where students learn through practice.…”
Section: Pedagogical Strategiesmentioning
confidence: 99%
“…Numerous studies have been conducted to illustrate reasonably valid indicators of students studying statistics who are likely to fail (Alston, Lane & Wright (2014); Elder, Jacobs & Fast (2015); Dupuis et al (2012); Duru, Duru & Balkis (2014); Galagedera, Woodward & Degamboda (2000); Macher, Paechter et al [2013]; Ratanaolarn (2016)).…”
Section: Literature Reviewmentioning
confidence: 99%